2007
DOI: 10.1039/b702724a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning second-order NLO responses through halogen bonding

Abstract: A theoretical and experimental approach to describing the influence of XB on the NLO properties of molecules in solution is given. As a function of the ability of the solvent to behave as acceptor of halogen bonding, the NLO-phores under study give rise to μβγ values ranging from+192x10-48 esu to -465x10-48 esu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 24 publications
3
67
0
1
Order By: Relevance
“…Calculations showed that the HOMO and LUMO, both -orbitals, are extended throughout the molecules, confirming an extended conjugation. The transition is associated with a chargetransfer interaction from a more polar ground state to a less polar excited state [19]. In agreement with the two state model mentioned above, positive values of hyperpolarizability in CHCl 3 were observed (μ for 10, 11, 12 are +124, +192, +173 x 10 -48 esu, respectively).…”
Section: Noncovalent Assembly As a Tool For Enhancing Eo Response In supporting
confidence: 69%
“…Calculations showed that the HOMO and LUMO, both -orbitals, are extended throughout the molecules, confirming an extended conjugation. The transition is associated with a chargetransfer interaction from a more polar ground state to a less polar excited state [19]. In agreement with the two state model mentioned above, positive values of hyperpolarizability in CHCl 3 were observed (μ for 10, 11, 12 are +124, +192, +173 x 10 -48 esu, respectively).…”
Section: Noncovalent Assembly As a Tool For Enhancing Eo Response In supporting
confidence: 69%
“…It is increasingly recognised that this interaction plays an important role in molecular recognition, biochemical processes and supramolecular chemistry. The applications include liquid crystals [2] and materials with specific non-linear optical [3,4] or magnetic [5,6] properties. In addition, halogen bonding plays a key role in the field of drug design [7,8] and protein-ligand complexation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the electron-withdrawing fluorines strongly enhances the electron acceptor ability of the organic iodine and in addition minimizes the interferences from the other weak interactions, the C-F groups being very insensitive to the interaction with other functional groups. This has permitted their application to dictate the arrangement of molecules for topological reactions in the solid state [30], for the creation of binding sites in crosslinked polymers [31], for layer-by-layer assembly of two polymers [32], for the design nonlinear optical materials [33] and liquid crystals [34], as anion receptors [35], for chiral resolution [36], for complex radicals to tune the magnetic interactions [37], and also for the controlled growth of thin films [38]. Nevertheless, the effectiveness of halogen bonds are not restricted to the use of haloperfluorocarbons; activation of the halogens can also be achieved by other means, such as sp hybridization of the carbon atom attached to the halogen or use of positively charged molecules, leading to novel materials with interesting properties.…”
Section: Halogens As Electrophilesmentioning
confidence: 99%